Detection of human growth hormone doping in urine: out of competition tests are necessary - Saugy, M.; Cardis, C.; Schweizer, C.; Veuthey, J. L.; Rivier, L. (Journal of Chromatography B: Biomedical Sciences and Applications, 1996)
The misuse of human growth hormone (hGH) in sport is deemed to be unethical and dangerous because of various adverse effects. Thus, it has been added to the International Olympic Committee list of banned substances. Until now, the very low concentration of hGH in the urine made its measurement difficult using classical methodology. Indeed, for routine diagnosis, only plasma measurements were available. However, unlike blood samples, urine is generally provided in abundant quantities and is, at present, the only body fluid allowed to be analysed in sport doping controls. A recently developed enzyme-linked immunosorbent assay (Norditest) makes it now possible, without any extraction, to measure urinary hGH (u-hGH) in a dynamic range of 2-50 ng hGH/l. In our protocol, untreated and treated non-athlete volunteers were followed. Some of them received therapeutical doses of recombinant hGH (Norditropin) for one week either intramuscularly (three increasing doses) or subcutaneously (12 i.u. every day). The u-hGH excretion after treatment showed dramatic increases of 50-100 times the basal values and returned to almost the mean normal level after 24 h. u-hGH was also measured in samples provided by the anti-doping controls at major and minor competitions. Depending on the type of efforts made during the competition, the hGH concentration in urine was dramatically increased. Insulin-like growth factor binding proteins and beta 2-microglobulins in urine and/or in blood could be necessary for the correct investigation of any hGH doping test procedure.